Accounting book of the Lviv Mint (1656–1657) as a source of accounting and analytical experience in managing business entities in emergencies - Shvets, V. (Видавництво Львівської політехніки, 2020)
Information for the management of economic entities is formed in accounting and does not lose its value in time for research and development of practical recommendations for the future. The Accounting Book of the Lviv Mint of 1656–1657, partially developed by historians, is a unique source of research and analytical experience in the management of public sector economic entities in emergencies, such as the war between the Polish-Lithuanian Commonwealth and Sweden (1655–1660). Unlike the books of merchants and artisans, keeping the Accounting Book at the Lviv Mint was mandatory, which testifies to the responsibility of its executors, and thus argues the authenticity of the reflected facts. The application of the rotary-historical method of studying the data of the Account Book in comparison with other historical and economic sources allows not only to reconstruct the events surrounding the opening of the Lviv Mint, but also to restore the sequence and targeting of management decisions to establish coin production in Lviv. The value source advantage of the Accounting Book is the use of in-kind, labor and cost measures, which allows to determine with sufficient accuracy all types of costs associated with the operation of the Lviv Mint and coinage. The participation of the king and the most influential elite of the Commonwealth at that time influenced the attraction of church property and private loans in the financing of the Lviv Mint in such an emergency situation as the war. The organization of cost accounting in the Accounting Book is built in chronological form, but characteristic of individual production processes, which is inherent in the minting of coins, which led to the use of cost accounting by places (centers) of their occurrence. Based on the data of the Accounting Book, the issues of payroll accounting, their types and composition of employees of the Lviv Mint were studied. Accounting and analytical data allow to determine the nature of management and logistics decisions for the production process and methods of external settlement operations at the Lviv Mint in emergency situations. Organizational and methodological bases of management decisions and their experience of accounting and analytical support of the Lviv Mint in the conditions of war have the prospect of use in modern emergencies, and in particular pandemics. This will mobilize management capacity and resources to reduce the risk of human losses from the spread of COVID-19 virus worldwide.
Keywords: Lviv Mint; accounting; accounting and analytical experience; Accounting book; management; M41; B15; 657(477)